Norway : Background Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Background Paper examines the medium-term economic outlook (1997-99) for Norway. The central feature of Norges Bank's reference case projection for the medium term is that the expansion of mainland output will slow from 3.3 percent in 1995 and 2.8 percent in 1996 to an annual average of 2 percent in 1997-99. Overall GDP growth will also slow from about 4 percent in each of 1995 and 1996 to 2 percent in 1997-99. Inflation is forecast to remain low, at 2 percent in 1996 and on average 2.3 percent per year in 1997-99.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet